Isolasi dan Karakterisasi Bakteri Amilotermofilik Dari Sumber Air Panas Sungai Medang - Pitri, Rahmadani Eka; Agustien, Anthoni; Febria, Fuji Astuti (Jurnal Biologi UNAND, 2015)
The research on isolation and characterization of amylothermophilic bacteria has been done in Research Laboratory of Microbiology, Biology Department, Mathematics and Natural Sciences Faculty, Andalas University, Padang. The aimed to obtain amylothermophilic isolate and describe their characteristic. The study used purposive sampling method and descriptive analysis. The study results obtained four amylothermophilic isolates with amylolitic index ranged from 2.23 until 3.51 were different macroscopic characters, rod shape, motile and produce catalase enzyme, three isolatesÂ wereÂ Gram positive and spore forming, one isolate wasÂ Gram negative.